Life-cycle environmental and cost-effective energy retrofitting solutions for office stock. (October 2020) - Gangolells, Marta; Gaspar, Katia; Casals, Miquel; Ferré-Bigorra, Jaume; Forcada, Nuria; Macarulla, Marcel
Highlights: A model to identify energy retrofitting measures for offices stock has been devised. Real reference offices are identified from energy performance certificate databases. Life-cycle energy, economic and environmental impacts are assessed. A user-friendly interface to support decision-makers is designed. Abstract: The European Green Deal establishes the need to renovate buildings in an energy efficient way, to address climate and environmental challenges. The purpose of this study was to devise a model for identifying environmental, cost-effective retrofitting measures by assessing their energy, economic and environmental impact when they are applied to the entire office stock. The methodology builds upon the energy performance certificate scheme to identify the life-cycle energy, economic and environmental impacts of a set of energy renovation measures for each representative office. The results can then be applied to the entire office stock. For any real office, a dozen characteristics are entered. Then, a user-friendly interface provides information about the expected performance of the renovation measures in that case along with the representativeness of the results. This methodology was implemented in a Spanish case study of 13, 701 energy performance certificates. The findings showed that the most efficient energy renovation measures are heat pump replacement (18.1 %) and replacement of lamps with LEDs (14.4 %). Although the most effective retrofitting solutions depended on the evaluation criteria (energy, economic or environmental), 99.5 % of the cost-effective measures also reduced emissions during the life cycle.